Role of Mindset on Human Behaviours in Relation to Leadership and Organizational Development - Rajesh, Sini (Digital Repository of Theses - SSBM Geneva, 2025)
This dissertation investigates the significance of mindset in influencing leadership behaviours, team dynamics, and organizational development, particularly within start-ups and Micro, Small and Medium-sized enterprises (MSMEs) in India. While the growth mindset theory has been extensively examined in educational and corporate environments, its relevance in smaller, non-Western organizational contexts has yet to be thoroughly explored. This research aims to fill these gaps by assessing the effects of growth mindset principles on leadership effectiveness, employee engagement, and overall organizational outcomes in MSMEs. Utilizing a mixed-methods approach, the study combines quantitative analysis of mindset intervention results with qualitative insights from interviews with leaders and business owners. The findings reveal that leaders with a growth mindset demonstrate greater adaptability, resilience, and receptiveness to feedback, enabling them to inspire and motivate their teams effectively. These leaders cultivate a culture of innovation, collaboration, and continuous learning, enhancing team performance and organizational development. In contrast, a fixed mindset correlates with limited creativity, resistance to change, and diminished team engagement. The research highlights mindset training programs' success in driving organizational behavioural and cultural transformations. Leaders who engaged in mindset workshops reported notable improvements in their ability to manage feedback, make adaptive decisions, and promote team innovation. Nevertheless, challenges such as resource limitations, cultural resistance, and deeply ingrained fixed mindset behaviours emerged as obstacles to the comprehensive implementation of mindset principles in MSMEs. By tackling the unique challenges MSMEs face and leveraging the transformative potential of growth mindset principles, the study offers actionable insights for leaders, practitioners, and policymakers. It emphasizes the importance of nurturing mindsetoriented leadership to achieve sustainable development and competitive advantages in the MSME sector, particularly in the Indian context. This dissertation concludes that growth mindset is crucial for driving organizational development in start-ups and MSMEs, laying the foundation for future research and practical applications in leadership and organizational development.